Bureaucratic Structure in Implementing the “Anggrek” Waste Bank Program in Larangan Village, Candi District, Sidoarjo Regency - Desy Widiyanti; Ilmi Usrotin Choiriyah (Indonesian Journal of Cultural and Community Development, 2021)
The environment is all forms that are around humans and can be an influence either directly or indirectly on human life. In order to realize waste management in accordance with applicable regulations, a waste bank program was created. One of the waste bank programs in Sidoarjo Regency is a waste bank in Larangan Village. One of the active waste banks in Larangan village is the “Anggrek” Garbage Bank which has received several award achievements. However, in its implementation the "Orchid" Waste Bank still has problems in the bureaucratic structure, there are still vacancies due to lack of human resources so that the management of dry and wet waste is still one-sided. This research was conducted with the aim of describing and analyzing the implementation of the "ANGGREK" Waste Bank Program in Larangan Village, Candi, Sidoarjo and knowing the supporting factors and obstacles. The research method used is descriptive qualitative method. The data obtained by interviews, field observations. Then the data is processed using qualitative analysis techniques where the data presented is not in the form of numbers, but in the form of words from the results of the data obtained (interviews, observations, and documentation) based on the Implementation of the "ANGGREK" Waste Bank Program in Larangan Village, Candi, Sidoarjo and then described and expanded. The results of the research on the Implementation of the "Orchid" Waste Bank Program in Larangan Village, Candi, Sidoarjo are that the bureaucratic structure of the "Orchid" waste bank program has the authority to carry out the weighing of the "Orchid" waste bank, the management carries out the authorities and responsibilities in accordance with applicable regulations. In terms of resources, there are still 4 people who are the administrators of the waste bank with 52 customers with limited human resources so that sometimes queues occur in the waste weighing process, while equipment resources have been provided at several points.